Correlation Between the Serum Sodium and Serum Magnesium Levels with Morbidity and Mortality in Case of Traumatic Brain Injuries - Mittal, Rahul; Mumtaz, Faisal; Faisal, Sumaiyya; Gupta, Shilpa (Asian Journal of Medical Research, 2018)
Background: Traumatic brain injury (TBI) occurs when outside force traumatically injures the brain. Traumatic brain injury is a major cause of mortality and morbidity worldwide. The aim of present study is to establish the relationship between the serum levels of sodium & magnesium and prognosis of patients of head injury in terms of mortality and morbidity. Subjects and Methods: This study compromise of all those cases who were admitted as a case of head injury through Neurosurgery outpatient department or through causality department of S.V.B.P hospital attached to LLRM medical college, Meerut during one year. All the factors producing mortality were found. Patients were followed-up and asked to come periodically. Outcome was recorded. Results: Patients who are admitted with poor GCS & those having higher Serum Sodium levels (More than 160 meq/ L) in posttraumatic period have poor prognosis and longer hospital stay. Patients who are admitted with poor GCS & those having lower serum Magnesium levels (less than 1.3 meq/L) have poor prognosis and longer hospital stay. In patients who have GCS of 13-15 serum sodium level is not increased much and there prognosis is better than those patients with GCS of 3-8 or 9-12. In patients who have GCS of 13-15 serum Magnesium level is not decreased much and there prognosis is better than those patients with GCS of 3-8 or 9-12. Conclusion: Serum sodium and magnesium levels are good prognostic markers for morbidity and mortality in case of traumatic brain injuries.